The role of microsurgical flaps in the treatment of burn patients – a single center experience - Gorecka, Zofia Malgorzata; Laczyk, Maciej; Majewski, Marek; Antonov, Sergey; Surowiecka, Agnieszka; Korzeniowski, Tomasz; Opalinski, Hubert; Torres, Kamil; Struzyna, Jerzy (Current Issues in Pharmacy and Medical Sciences, 2025)
Severe burns and electrical injuries pose significant challenges in reconstructive surgery, particularly when vital structures such as joints, tendons, nerves and bones are involved. Effective and timely coverage is essential to minimize complications and improve outcomes. The treatment approach includes methods such as conservative treatment, skin grafts, skin substitutes, local flaps and microsurgical free flaps. Each method has its limitations, especially in compromised tissues, where microsurgical flaps are most suitable. These are rarely used initially in burn treatment, but are more commonly employed in secondary reconstruction to address defects from scar contracture release. Microsurgical flaps offer better functional outcomes and a reduced risk of recurrent contractures compared to skin grafts or local flaps. They are a promising solution for severe burns, but pose a significant challenge to the surgeon. This is because microsurgical failure rates are higher in burn patients due to systemic inflammation affecting haemodynamics and haemostasis. Over the last 6 years, 10 microsurgical free flaps have been performed in burn patients at the East Centre of Burns Treatment and Reconstructive Surgery in Łęczna. The aim of this article is to describe our experience with microsurgical reconstruction in burns and to present a review the available literature.